Path to Empowerment: A Feminist Pedagogical Approach to Critical Civic Education in Early Childhood - Stanwick, Rebecca (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
School is often the first institutional experience where children learn to work collaboratively across social and cultural differences. However, civic education in the early childhood classroom often focuses on preparing students for future participation in society. By not allowing young children to critically engage with the reality of the world in which they live, many educators are creating a learning environment where children are not active in their knowledge making but are rather subjects that have knowledge placed upon them. Using a feminist pedagogical approach to critical civic education, this paper explores how defying the normative white patriarchal classroom structure can create a civic consciousness that empowers young people, especially girls, to active citizenship. With an emphasis on cooperative learning, student voice, critical engagement, and democratic education a feminist approach to critical civic education creates a learning environment that promotes collaboration rather than competition while fostering an activist spirit that transforms students into change-makers.